2018
DOI: 10.1016/j.pmrj.2018.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐Response Effects of Tai Chi and Physical Therapy Exercise Interventions in Symptomatic Knee Osteoarthritis

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 65 publications
(96 reference statements)
1
19
0
Order By: Relevance
“…[14] Studies have shown that Tai Chi has produced beneficial effects for treating KOA, such as reducing pain, improving physical function, reducing depressed mood and improving quality of life. [8,[15][16][17] The analgesic effect of Tai Chi on CPKOA has been confirmed by an increasing number of reports. The analgesic effect of Tai Chi on CPKOA has been confirmed by more and more reports, [14,18] thus showing the application prospect of Tai Chi in the clinical practice of CPKOA.…”
Section: Introductionmentioning
confidence: 81%
“…[14] Studies have shown that Tai Chi has produced beneficial effects for treating KOA, such as reducing pain, improving physical function, reducing depressed mood and improving quality of life. [8,[15][16][17] The analgesic effect of Tai Chi on CPKOA has been confirmed by an increasing number of reports. The analgesic effect of Tai Chi on CPKOA has been confirmed by more and more reports, [14,18] thus showing the application prospect of Tai Chi in the clinical practice of CPKOA.…”
Section: Introductionmentioning
confidence: 81%
“…Notably, the Tai Chi group demonstrated superiority in terms of depression and the physical component in quality of life. Secondary analysis of the same trial concluded that patients begin to notice the improvements after 2-5 wk[ 8 ]. Other studies have also supported the effectiveness of yoga in KOA.…”
Section: Exercisementioning
confidence: 99%
“…Compared with other conventional physical therapy, Tai Chi has a better treatment effect on reducing depression ( Li et al, 2020 ). The shortest adequate treatment time of Tai Chi for patients with KOA is 2–5 weeks ( Lee et al, 2018 ). A clinical experiment showed that Tai Chi can change KOA patients’ gait and plantar pressure load pattern during walking ( Zhang et al, 2020 ).…”
Section: Exercise Training and Koamentioning
confidence: 99%